Strata migration and fracture development under continuous extraction and continuous backfill with CO2 mineralized backfill materials - Yujun Xu; Liqiang Ma; Yangyang Wang; Jiangtao Zhai; Zhiyang Zhao (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract CO2 carbonation is currently restricted in laboratory instead of industrial application at ambient conditions. Meanwhile, few evaluations for safe storage have been made after CO2 carbonation backfill. Herein, the continuous extraction and continuous backfill (CECB) with CO2 mineralization backfill materials (CMBM) to storage CO2 was proposed. The CMBM samples were prepared and the uniaxial compressive strength (UCS) and CO2 uptake rates at various curing times and fly ash (FA)/gangue ratios were tested. The early and later strength at all ratios is more than 1 and 3.6 MPa, respectively, satisfying the requirements in underground backfill. A higher FA proportion means a higher UCS and a more significant effect of curing time on UCS as the hydration products of cement and FA contribute primarily to the early and later strength, respectively. As FA content rises, the CO2 uptake rate increases from 3.55 to 4.25 mg-CO2/g-CMBM since the alkaline oxides such as CaO in FA are higher than those in gangue. An analogue model was then constructed to simulate the overburden deformation. The ratio of the similar materials of CMBM at 7 d and F6G4 was determined to Water: Sand: CaCO3: CaSO4 of 3.56: 13.56: 0.94: 0.51. The maximum horizontal deformation of aquifuge is lower than the threshold value of 0.2–0.3 mm/m for preserving aquifer. The strain-softening parameters including cohesion, friction, dilation, and tensile strength were determined to be 0.54, 30°, 0, and 0 for UDEC simulation. The envelopes of water-conductive fractured zone (WCFZ) are saddle shaped, and the height of WCFZ is 4, 9.5, 17, and 26 m, respectively. After backfilling, there are still entire strata with thickness of 5 m between WCFZ and aquifer II. The research offers a novel way to dispose CO2 gas, solid wastes and mitigate overburden deformation, which is conducive to geological disposal of energy wastes.